2022
DOI: 10.1039/d1dt02988f
|View full text |Cite
|
Sign up to set email alerts
|

Terpyridine copper(ii) complexes as potential anticancer agents by inhibiting cell proliferation, blocking the cell cycle and inducing apoptosis in BEL-7402 cells

Abstract: Four mononuclear terpyridine complexes [Cu(H-La)Cl2]·CH3OH (1), [Cu(H-La)Cl]ClO4 (2), [Cu(H-Lb)Cl2]·CH3OH (3), and [Cu(H-Lb)(CH3OH)(DMSO)](ClO4)2 (4) were prepared and fully characterized. Complexes 14 exhibited higher cytotoxic activity against several tested cancer cell lines...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…The role played by Ca 2+ levels in cell apoptosis was examined using a fluorescent probe (Fluo-3Am) via flow cytometry. 43 To study the efflux of intracellular Ca 2+ induced by DQ6 (2.25 μM) and DQ11 (10.39 μM) over 24 h, we used Fluo-3Am as a special dye for determining intracellular Ca 2+ . The fluorescence intensity of SK-OV-3CR cells in the DQ6 - and DQ11 -groups was significantly enhanced (32.79 ± 0.78% and 21.28 ± 0.25%, respectively), indicating a notable increase in the intracellular Ca 2+ concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role played by Ca 2+ levels in cell apoptosis was examined using a fluorescent probe (Fluo-3Am) via flow cytometry. 43 To study the efflux of intracellular Ca 2+ induced by DQ6 (2.25 μM) and DQ11 (10.39 μM) over 24 h, we used Fluo-3Am as a special dye for determining intracellular Ca 2+ . The fluorescence intensity of SK-OV-3CR cells in the DQ6 - and DQ11 -groups was significantly enhanced (32.79 ± 0.78% and 21.28 ± 0.25%, respectively), indicating a notable increase in the intracellular Ca 2+ concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The annexin V-FITC/PI double staining assay was used to further investigate the mechanism of apoptosis induced by these Cu( ii ) complexes. 40 It determines the cell state by the change in the permeability and integrity of the cell membrane. 41 As can be observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gu et al prepared four terpyridine copper(II) complexes ( Figure 6 C), which exhibited higher cytotoxic activity against several tested cancer cell lines, especially BEL-7402 cells. They showed low toxicity to normal human liver cells [ 69 ]. Mechanistic studies have shown that copper complexes can induce G0/G1 phase arrest and alter the expression of cell cycle-related proteins.…”
Section: Application Of Novel Copper Complexes In Tumor Therapymentioning
confidence: 99%